Predicting Formation Pore-Pressure from Well-Log Data with Hybrid Machine-Learning Optimization Algorithms; Natural Resources Research; Vol. ХХ, iss. XX - Farsi M. Mohammad; Mohamadian N. Nima; Ghorbani H. Hamzeh; Wood D. A. David; Davoodi Sh. Shadfar; Moghadasi J. Jamshid; Ahmadi A. M. Alvar Mehdi (2021, 2021)
Title screen